Discovery of a small molecule inhibitor targeting dengue virus NS5 RNA-dependent RNA polymerase. - Hideaki Shimizu; Akatsuki Saito; Junko Mikuni; Emi E Nakayama; Hiroo Koyama; Teruki Honma; Mikako Shirouzu; Shun-Ichi Sekine; Tatsuo Shioda (Public Library of Science (PLoS), 2019)
Dengue is a mosquito-borne viral infection that has spread globally in recent years. Around half of the world's population, especially in the tropics and subtropics, is at risk of infection. Every year, 50-100 million clinical cases are reported, and more than 500,000 patients develop the symptoms of severe dengue infection: dengue haemorrhagic fever and dengue shock syndrome, which threaten life in Asia and Latin America. No antiviral drug for dengue is available. The dengue virus (DENV) non-structural protein 5 (NS5), which possesses the RNA-dependent RNA polymerase (RdRp) activity and is responsible for viral replication and transcription, is an attractive target for anti-dengue drug development. In the present study, 16,240 small-molecule compounds in a fragment library were screened for their capabilities to inhibit the DENV type 2 (DENV2) RdRp activities in vitro. Based on in cellulo antiviral and cytotoxity assays, we selected the compound RK-0404678 with the EC50 value of 6.0 μM for DENV2. Crystallographic analyses revealed two unique binding sites for RK-0404678 within the RdRp, which are conserved in flavivirus NS5 proteins. No resistant viruses emerged after nine rounds of serial passage of DENV2 in the presence of RK-0404678, suggesting the high genetic barrier of this compound to the emergence of a resistant virus. Collectively, RK-0404678 and its binding sites provide a new framework for antiviral drug development.